2015
DOI: 10.1038/jid.2015.12
|View full text |Cite
|
Sign up to set email alerts
|

An Autosomal Recessive Mutation of DSG4 Causes Monilethrix through the ER Stress Response

Abstract: Monilethrix is a hair shaft anomaly characterized by beaded hair with periodic changes in hair thickness. Mutations in the desmoglein 4 (DSG4) gene reportedly underlie the autosomal recessive form of the disease. However, the pathogenesis and cellular basis for the DSG4 mutation-induced monilethrix remained largely unknown. We report a Japanese female patient with monilethrix. Observation of her hair shaft by means of transmission electron microscopy showed fewer desmosomes and abnormal keratinization. Genetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 32 publications
0
20
0
1
Order By: Relevance
“…Some authors suggest that desmoglein 4 may play a role as an additional autoantigen in pemphigus vulgaris [ 9 ]. Mutations in Dsg4 gene are responsible for localized autosomal recessive hypotrichosis [ 11 ], monilethrix [ 12 ], and in some cases an overlap of both [ 13 ]. Schaffer et al reported three cases of localized autosomal recessive hypotrichosis and monilethrix in combination with scalp erosions presenting mutations in the gene for desmoglein 4 [ 14 ].…”
Section: Resultsmentioning
confidence: 99%
“…Some authors suggest that desmoglein 4 may play a role as an additional autoantigen in pemphigus vulgaris [ 9 ]. Mutations in Dsg4 gene are responsible for localized autosomal recessive hypotrichosis [ 11 ], monilethrix [ 12 ], and in some cases an overlap of both [ 13 ]. Schaffer et al reported three cases of localized autosomal recessive hypotrichosis and monilethrix in combination with scalp erosions presenting mutations in the gene for desmoglein 4 [ 14 ].…”
Section: Resultsmentioning
confidence: 99%
“…For the immunoprecipitation analyses, the cells were lysed in 1% NP-40/Tris-buffered saline (TBS) supplemented with protease inhibitor cocktail (Roche) and incubated with anti-FLAG M2 affinity gel (Sigma, St Louis, MO, USA) for overnight at 4 C. The agarose beads were washed with lysis buffer five times. The cell lysates, culture media and immunoprecipitate were separated on 7.5% SDS gels (Bio-Rad, Hercules, CA, USA), and immunoblotting was performed as previously described [17].…”
Section: Plasmid Constructionmentioning
confidence: 99%
“…Four genes are associated with monilethrix and are responsible for autosomal dominant transmission of the disease [1,2]. An autosomal recessive form has also been described and is caused by mutations of gene DSG4 coding for desmoglein 4 [3]. The diagnosis of monilethrix was more difficult to establish in our patient owing to the absence of any familial cases.…”
Section: Case Discussionmentioning
confidence: 84%